ANALISIS PENGARUH BUDAYA ORGANISASI DAN ETOS KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS DINAS KELAUTAN DAN PERIKANAN DAERAH ISTIMEWA YOGYAKARTA) - Nofika Amalia; Puji Astuti (Universitas Ahmad Dahlan, 2020)
This study aims to determine the effect of organizational culture and work ethic on employee performance in the Department of Maritime Affairs and Fisheries of the Special Region of Yogyakarta. This research was conducted in March to April 2019. The sample used in this study were all employees, amounting to 57 people. The sampling technique uses the saturated sample method or takes the entire total population. Data collection methods used were qualitative using a questionnaire. Data analysis techniques in this study used the analysis of the research instrument test, classic assumption test, multiple linear regression test, partial test (t test), simultaneous test (f test), and coefficient of determination test. Multiple linear analysis is used to test the hypothesis of this study. The results showed that: (1) Organizational culture has a positive and significant effect on employee performance (Y), as evidenced by the t-count value of organizational culture of 2.986> t-table 2.004. (2) Work ethic has a positive and significant effect on employee performance (Y), as evidenced by the value of t-work ethic of 0.386 > t-table 2.004. (3) Organizational culture and work ethics simultaneously have a significant effect on employee performance as evidenced by the f-count value of 22.723 > f-table 3.16. The adjusted R square variant value = 0.437 or 43.7%, meaning that the organizational culture and work ethic variables are able to explain the employee performance variable of 43.7%, while the remaining 56.3% is explained by other variables not examined in this study.